THE IMPACT OF INTELLIGENT AUTOMATION ON MODERN BUSINESS OPERATIONS: A DATA-DRIVEN ANALYSIS - Devesh Gupta (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article presents a comprehensive analysis of intelligent automation's transformative role in modern enterprise operations, examining implementation patterns across diverse industry sectors from 2020 to 2024. Through quantitative analysis of 500+ enterprise implementations, we identify three key patterns: (1) the emergence of hybrid automation architectures combining on-premise and cloud solutions, achieving 42% higher performance than traditional single-mode deployments; (2) a correlation between automation maturity and business resilience, with organizations at advanced automation stages showing 3.5x better adaptability to market disruptions; and (3) the critical role of data architecture in automation success, with organizations employing unified data platforms reporting 65% higher ROI on automation investments. Our analysis reveals that successful intelligent automation implementations follow a distinct maturity curve, progressing through stages of task automation, process automation, and cognitive automation. The article also highlights emerging challenges, including data privacy concerns, ethical considerations in AI decision-making, and the growing skills gap in automation expertise. By examining real-world case studies across financial services, healthcare, and manufacturing sectors, we provide actionable insights for organizations at various stages of their automation journey. This article contributes to the field by establishing quantifiable metrics for automation success and proposing a framework for sustainable intelligent automation implementation in enterprise environments.